Radio-Induced Maxillary Angiosarcoma: About a Case - Hachemi, Mohamed; Zohra Touarigt, Fatma; Hireche, Lina; Oukaour, Lylia (Journal of Otolaryngology Advances, 2025)
Introduction Angiosarcoma is a rare malignant tumour from fast-evolving and aggressive vascular endothelial cells that accounts for 1% of all sarcomas. The sinus location of angiosarcoma is exceptional. The clinical polymorphism of this tumour may cause a delay in diagnosis. Risk factors are not always understood. However, a history of radiation therapy for locoregional cancer and/or lymphedema is most commonly found. The prognosis remains bleak with an overall five-year survival of 35 to 40%. Objectives The authors discuss the diagnostic, therapeutic and prognostic modalities and difficulties of this tumour. Observation: The authors report a case of maxillary sinus angiosarcoma confirmed by radio-induced secondary CD34 immunohistological staining in a 40-year-old man having a history of hemangioendothelioma treated with conservative endoscopic surgery and adjuvant radiotherapy 15 months earlier. Discussion This lesion is rare in the ENT sphere and may be confused with a benign tumor in its early stages. Only histological examination with immunohistochemistry can confirm the diagnosis (factor VIII, CD34 and CD31 antigens). Treatment consists of a wide resection followed by radiotherapy, hence the need for early diagnosis in the metastatic phase, first-line treatments include doxorubicin or paclitaxel weekly. Conclusion Radio-induced angiosarcoma is a rare malignant tumour, it occurs in patients who have received conservative treatment and radiation therapy for nasosinusitis cancers. Angiosarcomas of the nasal passages remain a diagnostic and therapeutic challenge due to their local and general aggressiveness.
Keywords: Angiosarcoma; Radio induced; Para nasal sinuses; immunohistochemistry; propranolol; clinical case